Heritage language and linguistic theory - Scontras, Gregory; Fuchs, Zuzanna; Polinsky, Maria (Frontiers in Psychology, 2015)
This paper discusses a common reality in many cases of multilingualism: heritage speakers, or unbalanced bilinguals, simultaneous or sequential, who shifted early in childhood from one language (their heritage language) to their dominant language (the language of their speech community). To demonstrate the relevance of heritage linguistics to the study of linguistic competence more broadly defined, we present a series of case studies on heritage linguistics, documenting some of the deficits and abilities typical of heritage speakers, together with the broader theoretical questions they inform. We consider the reorganization of morphosyntactic feature systems, the reanalysis of atypical argument structure, the attrition of the syntax of relativization, and the simplification of scope interpretations; these phenomena implicate diverging trajectories and outcomes in the development of heritage speakers. The case studies also have practical and methodological implications for the study of multilingualism. We conclude by discussing more general concepts central to linguistic inquiry, in particular, complexity and native speaker competence.